Association of Gender and Body Mass Index With Hemorrhoid Recurrence at Pelambuan Public Health Center, Banjarmasin - Aisyah, Siti; Afriyanti, Uni; Sary, Era Widia; Hadriyanti, Dessy (Fakultas Kedokteran, Universitas Papua, 2025)
Non-communicable diseases are a major health burden in developing countries, one of which is hemorrhoids. Hemorrhoids are abnormal anorectal conditions commonly characterized by anal bleeding. Hemorrhoids have the highest recurrence rate among anorectal disorders. Various factors may contribute to hemorrhoid recurrence, including gender and body mass index (BMI). In males, hemorrhoids may be caused by more intense physical activity, while in females, they may be influenced by the hormone progesterone, which inhibits contractions in the digestive tract. Excess BMI or body fat levels can lead to increased intra-abdominal pressure, which is considered a contributing factor to hemorrhoid recurrence. This study aimed to determine the association of gender and body mass index with hemorrhoid recurrence at Pelambuan Public Health Center, Banjarmasin. A correlational analytical design with a cross-sectional approach was employed, involving total sampling of 83 respondents with a history of hemorrhoids. Data were collected using a questionnaire. Analysis using the Chi-Square statistical test showed a significant association between gender and hemorrhoid recurrence (p = 0.035 < α = 0.05), as well as between body mass index and hemorrhoid recurrence (p = 0.001 < α = 0.05). It is concluded that gender and body mass index are significantly associated with hemorrhoid recurrence. Hemorrhoid sufferers are advised to maintain regular physical activity, a healthy body weight, nutritious eating habits, and avoid excess fat accumulation as preventive measures against recurrence.